Empirical Descriptions of Criminal Sentencing Decision-Making - Wandall, Rasmus H. (Bergen Journal of Criminal Law & Criminal Justice, 2014)
The article addresses the widespread use of statistical causal modelling to describe criminal sentencing decision-making empirically in Scandinavia. The article describes the characteristics of this model, and on this basis discusses three aspects of sentencing decision-making that the model does not capture: 1) the role of law and legal structures in sentencing, 2) the processes of constructing law and facts as they occur in the processes of handling criminal cases, and 3) reflecting newer organisational changes to sentencing decision-making. The article argues for a stronger empirically based design of sentencing models and for a more balanced use of different social scientific methodologies and models of sentencing decision-making.